Aktivitas Perempuan Petani Sayuran di Desa Kaballokang Pakkabba Kabupaten Takalar - Abdul Rahman (PT. ALHAFI BERKAH INDONESIA, 2024)
This research aims to analyze the activities of women in Kaballokang Pakkabba Village choosing to work as vegetable farmers, and the implications of women vegetable farmers on the pattern of division of labor in Kaballokang Pakkabba Village. This research uses observation, interviews and documentation methods. The results of the research show that women choose to work as vegetable farmers due to various factors both in terms of economics, family factors, the type of female worker, and environmental condition factors, housewives' strategies in dividing their time, namely some start cleaning the house first and then start working as vegetable farmers. There are also those who work first taking care of vegetable plants and then doing work in the domestic area of ​​the household. Working as a vegetable farmer can be sustainable because of the support of close family, namely husband, parents and in-laws, children and neighbors.